2017
DOI: 10.1177/0040517517697639
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide as a green media in textile dyeing: A review

Abstract: This review highlights the great role of supercritical carbon dioxide fluid technology in textile dyeing processes. The unequivocal physical characteristics of supercritical carbon dioxide are presented and further researched to continue the development of high efficiency, compact dyeing to save energy and water in manufacturing processes. This review also focuses on the solubility of the dyes in scCO2 as well as the application of the technology to both synthetic and natural fabrics. Some factors relating to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 115 publications
(194 reference statements)
1
44
0
Order By: Relevance
“…In the previous work (Long et al, 2011;Long et al, 2012;Van der Kraan et al, 2007), water pre-treatment and water addition were shown to improve the dyeing results dramatically. The dyeing time and temperature had great impact on the dyeing qualities (Bach et al, 2002). Thus, in this study, the amount of water, dyeing time and temperature was quantified in order to establish the best dyeing conditions of the RD 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous work (Long et al, 2011;Long et al, 2012;Van der Kraan et al, 2007), water pre-treatment and water addition were shown to improve the dyeing results dramatically. The dyeing time and temperature had great impact on the dyeing qualities (Bach et al, 2002). Thus, in this study, the amount of water, dyeing time and temperature was quantified in order to establish the best dyeing conditions of the RD 1.…”
Section: Resultsmentioning
confidence: 99%
“…The dyeing conditions for dyeing both wool and cotton were much milder than those in the literature, indicating that there is a potential to try industrial scale experiments with this dyeing method (Abou Elmaaty and Abd El-Aziz, Bach et al, 2002;Banchero, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SFD is not a novelty since its first experiments date back to the 1980s; comprehensive reviews can be found in the literature 8‐10 . This work is mainly focused on the recent advances of this technology from 2014 to the present.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The application of supercritical carbon dioxide in the textile eld has also shown its advantage for replacing the environmentally unfriendly aqueous dyeing process because of the low energy consumption and zero waste water emission. [10][11][12][13][14] Former experiments veried that during supercritical carbon dioxide dyeing process, the addition of water always performs the improvement effects for natural bers dyeing. Firstly, a certain amount of water in supercritical carbon dioxide can alter the chemical nature (polarity and pH) of the uid, thus affecting the solubility and reactivity of dyes.…”
Section: Introductionmentioning
confidence: 99%